2015
DOI: 10.1021/jacs.5b05637
|View full text |Cite
|
Sign up to set email alerts
|

Toward Multiple Conductance Pathways with Heterocycle-Based Oligo(phenyleneethynylene) Derivatives

Abstract: In this paper, we have systematically studied how the replacement of a benzene ring by a heterocyclic compound in oligo(phenyleneethynylene) (OPE) derivatives affects the conductance of a molecular wire using the scanning tunneling microscope-based break junction technique. We describe for the first time how OPE derivatives with a central pyrimidine ring can efficiently link to the gold electrode by two pathways presenting two different conductance G values. We have demonstrated that this effect is associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
75
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 72 publications
9
75
1
Order By: Relevance
“…As depicted in Figure 1 C, the presence of the nitrogen atom shows no distinguishable effect on the constructive QI in the junctions through the para ‐coupled molecules p ‐OPE and P , which is in good agreement with Ref. 7c and the results obtained by Gonzalez et al 7b…”
supporting
confidence: 91%
See 1 more Smart Citation
“…As depicted in Figure 1 C, the presence of the nitrogen atom shows no distinguishable effect on the constructive QI in the junctions through the para ‐coupled molecules p ‐OPE and P , which is in good agreement with Ref. 7c and the results obtained by Gonzalez et al 7b…”
supporting
confidence: 91%
“…Interestingly, there is no significant conductance feature of the molecular junctions with one of Au electrodes connected directly to the central pyridine ring via the Au−N bonds, as observed in the analogous system containing a pyrimidine ring 7b. This observation can be attributed to the significant binding force difference between the Au−S covalent bond (1.2 nN)10 and the Au−N bond (0.8 nN)11 that is close to the Au−S (methylsulfide) bond (0.7 nN),12 leading to a preference for the covalent Au−S over the Au−N binding motif in the present case.…”
mentioning
confidence: 89%
“…17,18,38 Experimental observables include conductance values and the most probable electrode separations at which they occur (Fig. 3C).…”
Section: Resultsmentioning
confidence: 99%
“…By substituting the central benzene ring with sulfur and nitrogen heterocycles, the authors were able to demonstrate a new high conductance channel formed by the linking of the central pyrimidine ring to the electrodes. 18 More recently, Kiguchi and co-workers have also shown the existence of 3 conductance states within a tripyridyl–triazine molecular junctions. 38 In the studies above 17,18,38 single circuits were assigned to each conductance state observed in the experiments and upto 3 circuits across the molecular scaffold were proposed to be accessible by the experiments.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation